2007
DOI: 10.1074/jbc.m611824200
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Structure of Deinococcus Bacteriophytochrome Yields New Insights into Phytochrome Architecture and Evolution

Abstract: Phytochromes are red/far red light photochromic photoreceptors that direct many photosensory behaviors in the bacterial, fungal, and plant kingdoms. They consist of an N-terminal domain that covalently binds a bilin chromophore and a C-terminal region that transmits the light signal, often through a histidine kinase relay. Using x-ray crystallography, we recently solved the first three-dimensional structure of a phytochrome, using the chromophore-binding domain of Deinococcus radiodurans bacterial phytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
444
3
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 224 publications
(492 citation statements)
references
References 53 publications
39
444
3
6
Order By: Relevance
“…In both states, four protons bound to the tetrapyrrole nitrogens are well resolved and can be assigned straightforwardly according to our previous studies (18) (Datasets S1 and S2). The absence of cross-peaks involving carboxylate protons (C8 3 and C12 3 ) in our data indicates that these side chains are deprotonated, implicated by earlier studies (19)(20)(21)29).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In both states, four protons bound to the tetrapyrrole nitrogens are well resolved and can be assigned straightforwardly according to our previous studies (18) (Datasets S1 and S2). The absence of cross-peaks involving carboxylate protons (C8 3 and C12 3 ) in our data indicates that these side chains are deprotonated, implicated by earlier studies (19)(20)(21)29).…”
Section: Resultssupporting
confidence: 63%
“…Early NMR spectroscopic studies on proteolytic phytochrome fragments (12,13) indicated that this isomerization occurs at the C15═C16 double bond (for numbering, see Fig. 1A), a geometrical change in line with vibrational spectroscopic investigations (14)(15)(16) and results from recent 13 C solid-state NMR (17,18) in which the most significant changes during the light-triggered conversions are confined to rings C and D. Exact geometries of the chromophore in the Pr state have been resolved as periplanar ZZZssa configurations in bacteriophytochromes from Deinococcus radiodurans (19) and Rhodopseudomonas palustris (20) as well as in the more plant-phytochrome-like Cph1 from the cyanobacterium Synechocystis 6803 (21). On the other hand, the crystal structure of the unusual bacteriophytochrome PaBphP Pseudomonas aeruginosa (22) whose ground state is Pfr shows a ZZEssa conformation, consistent with the expected primary photochemistry at the C15═C16 double bond (Fig.…”
mentioning
confidence: 75%
“…SEC supported an elongated shape for the crystallographic subunits by estimating a Stokes radius ∼1.3 times that predicted. Analogous to several BphPs (12,13,17), the dimerization interface involved the GAF domain α1/α2/α6-helical bundle ( Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Arabidopsis PhyB PSM structure (Protein Data Bank ID code 4OUR) shares its core PAS-GAF-PHY domain architecture with canonical BphPs/Cphs (9,(11)(12)(13) with the inclusion of unique features in each domain (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Both the branch-site test and the character mapping exercise identify the sequence coordinates of change, and these can be evaluated in the light of crystal structures that have recently been presented (Wagner et al, , 2007Yang et al, 2007Yang et al, , 2008Cornilescu et al, 2008;Essen et al, 2008;Ulijasz et al, 2010) and can be compared with known mutants. Currently, high-resolution structures of the photosensory core of prokaryotic phytochromes are available; this region is homologous with the sensory module of plant phytochromes (Montgomery and Lagarias, 2002;Lamparter, 2004;Karniol et al, 2005) and consists of PAS, GAF, and PHY domains ( Figure 3B).…”
Section: Synthesis Of Functional Evolutionary and Structural Datamentioning
confidence: 99%